On Many Routes : Internal, European, and Transatlantic Migration in the Late Habsburg Empire - Steidl, Annemarie, 1965- (Book collections on Project MUSE., 2021)
"On Many Routes is about the history of human migration. With a focus on the Habsburg Empire, this innovative work presents an integrated and creative study of spatial mobilities: from short to long term, and intranational and inter-European to transatlantic. Migration was not just relegated to city folk, but likewise was the reality for rural dwellers, and we gain a better understanding of how sending and receiving states and shipping companies worked together to regulate migration and shape populations. Bringing historical census data, governmental statistics, and ship manifests into conversation with centuries-old migration patterns of servants, agricultural workers, seasonal laborers, peddlers, and artisans-both male and female-this research argues that Central Europeans have long been mobile, that this mobility has been driven by diverse motivations, and that post-1850 transatlantic migration was an obvious extension of earlier spatial mobility patterns. Demonstrating the complexity of human mobility via an exploration of the links between overseas, continental, and internal migrations, On Many Routes shows that migrations to the United States, to the nearest coalfield, and to the urban capitals are embedded within complicated patterns of movement. There is no good reason to study internal apart from transnational moves, and combining these fields brings ample possibility to make migration research more relevant for the much broader field of social and economic history. This work poses an invaluable resource to the understudied area of Habsburg Empire migration studies, which it relocates within its wider European context and provides a major methodological contribution to the history of human migration more broadly. The ubiquity and functionality of human movement sheds light on the relationship between human nature and society, and challenges simplistic notions of human mobility then and now"--